Design of a Double-decker Rotating Flexible Hinge - Zhanning Zhang; Jing Zhang; Ziming Kou (Jixie chuandong)
To increase off-axis stiffness and rotating angle, a double-decker rotating flexible hinge is designed, with straight beams and curved plates combined as the flexible body. The model of rotational stiffness is established by pseudo rigid model of fixed-oriented beam and the equivalent method of series and parallel spring. The model of off-axis stiffness is established by the pseudo rigid body method. Then a finite element simulation model is established by using ANSYS software, and compared with the theoretical model. The results show that the rotational stiffness error is about 7% and the off-axis stiffness error is about 3%, which can prove the correctness of the stiffness models. The statics performance of the flexible hinge is clear by analyzing rotating stiffness and off-axis stiffness, whose off-axis stiffness is 2 N/mm and rotating angle is 30°.